Preliminary Discussion on the Anticipatory Governance of Ethical Risks in Medical New-quality Advanced Technologies - Chen WANG; Fei XU (Yixue yu zhexue, 2025)
With the rapid advancement of medical new-quality advanced technologies, the ethical risks they trigger have manifested novel systemic, irreversible, and intergenerational characteristics, posing formidable challenges to traditional "post-hoc remediation" governance models. Anticipatory governance theory offers a novel pathway to reconcile the tension between technological innovation and ethical order. This approach advocates embedding ethical reflection at the initial stages of technology development. Through foresight mechanisms, engagement mechanisms, and integration mechanisms, it constructs a resilient governance ecosystem that fosters co-evolution between technology and society. The findings reveal that medical technological development must not transgress the sacred boundaries of human dignity. Only by institutionalizing the ethical principle of "humans as ends in themselves" through anticipatory governance—can medical new-quality advanced technologies genuinely serve the protection of life dignity, rather than becoming subservient to capital interests and extreme instrumental rationality.